Bioelectricity generation in a microbial fuel cell using polypyrrole-molybdenum oxide composite as an effective cathode catalyst. (1st September 2020) - Karthick, S.; Haribabu, K.
Graphical abstract: Highlights: Ppy/MoO2 composite coated over carbon cloth was used as an electrode in SCMFC. Charge transfer and oxygen reduction reaction were enhanced by Ppy/MoO2 composite. Ppy/MoO2 catalyst shows comparable MFC performance to the platinum catalyst. Abstract: This study investigates the performance of Polypyrrole/molybdenum oxide (Ppy/MoO2 ) composite as a cathode catalyst in a single chamber microbial fuel cell (SCMFC). The prepared catalyst composite was characterized by X-Ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Field-emission scanning electron microscopy (FE-SEM), and Energy dispersive X-Ray spectroscopy (EDS) which demonstrate the unique nature and purity of the material. The high charge transfer capacity and oxygen reduction reaction (ORR) of the Ppy/MoO2 cathode catalyst was confirmed by cyclic voltammetry (CV), electron impedance spectroscopy (EIS), and Tafel analysis. The open-circuit potential of SCMFC by using Ppy/MoO2 (2:1) cathode catalyst (0.688 V) was 1.8 times higher than that of carbon cloth (0.380 V). The inferred results suggest that Ppy/MoO2 catalyst is a potential alternative to Pt in SCMFC for power generation.